2010
DOI: 10.1108/13217341011059417
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional audit behaviour: an exploratory study in Malaysia

Abstract: PurposeThe quality of the opinion provided by audit firms is an important determinant of their long‐term survival, but audit quality is difficult to gauge, which makes it particularly sensitive to the behaviour of the individuals who carry on audit work. This paper seeks to identify the incidence of dysfunctional audit behaviours and audit quality reduction behaviours, actions taken by an auditor during engagement that reduce evidence‐gathering effectiveness.Design/methodology/approachThe paper is based on a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0
15

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(73 citation statements)
references
References 14 publications
5
53
0
15
Order By: Relevance
“…This relationship is stronger in environments where employees assume there is too much supervisory control (Gable, 1994). Use of auditing programs, time budgets and close supervision could turn the auditing process into an extremely structured process (Smith, 2012). Performance parameters have also been employed in this study since they were employed in previous studies as well and their relevance was established (Donnelly, 2003).…”
Section: Direct Relationship With the Acceptance Of Dabmentioning
confidence: 99%
See 3 more Smart Citations
“…This relationship is stronger in environments where employees assume there is too much supervisory control (Gable, 1994). Use of auditing programs, time budgets and close supervision could turn the auditing process into an extremely structured process (Smith, 2012). Performance parameters have also been employed in this study since they were employed in previous studies as well and their relevance was established (Donnelly, 2003).…”
Section: Direct Relationship With the Acceptance Of Dabmentioning
confidence: 99%
“…These behaviors provide a tool for auditors to manipulate the auditing process (Donnelly, 2003). Locus of control has been employed in behavioral researches extensively to explain human behaviors in organizational contexts (Smith, 2012). Donnelly et al (2003) indicated that individuals have general expectations with regard to the question that whether success in a certain situation depends on individual behavior or is controlled by external forces.…”
Section: Direct Relationship With the Acceptance Of Dabmentioning
confidence: 99%
See 2 more Smart Citations
“…Auditors' behaviour is reflective of his personality and individual characteristics when performing audit service [4]. Reference [5] argue that more ethical oriented individuals are more motivated in their intention to behave ethically than less ethical oriented people.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%